0632 Analysis of Sleep Bout Duration: A New Marker to Differentiate Narcolepsy Type 1. (27th April 2018) - Honda, M; Ito, W; Ueno, T; Wada, M; Narisawa, H; Kato, N
Abstract: Introduction: Recent studies reported the diagnostic value of sequential occurrence of sleep stages (stage transition) in addition to the conventional sleep macrostructure (sleep onset REM period) for diagnosis of narcolepsy type 1. However these analyses did not utilize the information of bout duration which may potentially serve as a marker for sleep stage continuity. We focused on the variation of bout (episode) duration in the nocturnal PSG records from hypersomnia patients to investigate the clinical relevance and found the specific changes in subjects with narcolepsy type1. Methods: Data were obtained from nocturnal PSG data of 460 consecutive subjects who underwent diagnostic PSG during Oct 2014 to Nov 2017 for the differential diagnosis of hypersomnia. After exclusion of cases with medication and comorbid sleep disorders, total 207 subjects (M/F=123/84, age 26.5(9.1) mean(SD)) with written informed consent were included in this study (29 narcolepsy type1, 30 narcolepsy type2, 63/49 idiopathic hypersomnia with/without long sleep time, 36 non hypersomnia control. To further evaluate the continuity / stability of nocturnal sleep PSG, we analyzed bout counts of each sleep stage, mean bout duration (min), and median values of all NREM and REM sleep episodes. We additionally calculated the correlation of these variables with subjective and objective sleep quality indexes. Results: Narcolepsy type 1 showed significant increase in N1 mean bout duration (1.54(0.54) vs 1.13(0.35) min) and significant decrease in REM mean bout duration (9.10(2.73) vs 13.43(4.57) min) compared to other conditions. N1 and REM sleep median values showed the similar significant changes (long N1: 2.40(1.20) vs 1.55(0.78) min and short REM: 13.20(4.9) vs 19.20(6.21) min) in narcolepsy type1. We confirmed that both markers were correlated with perceived number of nocturnal awakenings and also showed good correlation with sleep transition index in each sleep stage. Conclusion: Our new analyses revealed the diagnostic value of sleep bout duration, which could reflect the REM sleep instability and compensatory increase in N1 sleep in narcolepsy type1. Further clinical relevance of these bout length markers are required. Support (If Any): None.